Soil chemical attributes in coffee growing with different agronomic techniques - Voltolini, Giovani Belutti; Silva, Larissa Cocato da; Alecrim, Ademilson de Oliveira; Castanheira, Dalyse Toledo; Resende, Laís Sousa; Rezende, Tiago Teruel; Guimarães, Rubens José (Coffee Science - ISSN 1984-3909, 2020)
The objective was to evaluate the effects on soil chemical attributes in a coffee growing area, according to different agronomic techniques used and their associations. The experiment was conducted in the field, in an experimental area at the Department of Agriculture - DAG, in Lavras - MG, from January 2016 to October 2018. Coffee was planted in January 2016, with Mundo Novo IAC 379-19 coffee seedlings, with a spacing of 3.6 m between rows and 0.75 m between plants in the planting row. The factors under study were arranged in a 3x2x5 factorial scheme, making a total of 30 treatments. In the plots, three soil managements were randomized (soil cover with polyethylene film, soil cover with brachiaria grass and conventional management of spontaneous vegetation). In the subplots, two types of fertilizers used in the fertilization of coffee trees were tested (conventional and increased-efficiency fertilizer). In the sub-subplots, four soil conditioners were tested (coffee husk, phosphogypsum, water retention polymer, organic compost), and the control without conditioner. Aimed to evaluate soil chemical attributes in coffee growing with different agronomic techniques through the evaluation of: soil pH, phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), aluminum saturation (m) and base saturation (V%), by soil analysis carried out in October 2018 and leaf analysis in December 2018. It is noteworthy that the chemical attributes of the leaf were used only for principal component analysis through multivariate analysis. The use of fertilization (with conventional fertilizers or those with increased efficiency), combined with the application of organic compost or coffee husk, provide increased soil pH, as well as the use of ecological management of brachiaria grass. The use of organic compost as a soil conditioner increases phosphorus availability in the soil. Coffee husk, as a soil conditioner, is an efficient potassium source for the coffee crop. The use of organic compost and phosphogypsum increases the calcium and magnesium contents in the soil. The use of organic compost and coffee husk was efficient in increasing the base saturation (V%) grown with coffee. The use of organic compost, coffee husk and phosphogypsum reduced aluminum saturation in the soil. Treatments associated with the use of organic compost improve calcium, phosphorus and magnesium levels, increase pH and base saturation, besides decreasing aluminum saturation. Key words: Coffea arabica; soil managements; fertilizers; soil conditioners.